Parasternal anterior mediastinotomy - Delgado, Bolivar; Soto, José; Gateño, Nisso; Belloso, Roberto (Cirugía del Uruguay, 1978)
A 10-observation series leads the authors to revise this mediastine exploration technique, stressing its value for the purpose of diagnosis and evaluation of the mediastinal extension in intra-thoracic disorders especially in lung cancer. Its indications and its value are discussed in comparison with other procedures such as mediastinoscopy; it has a high positive rate and low morbimortality.